Rates of breastfeeding initiation and duration in the United States: data insights from the 2016-2019 Pregnancy Risk Assessment Monitoring System - Laura E. Diaz; Lynn M. Yee; Joe Feinglass (Frontiers Media S.A., 2023)
IntroductionWhile breastfeeding rates in the United States have been increasing, they remain low by international standards with substantial racial, income and education disparities. This study uses recent population-based data to analyze sociodemographic differences in breastfeeding initiation, duration, and exposure to information and education.MethodsWe used the 2016-2019 Pregnancy Risk Assessment Monitoring System (PRAMS) to compare breastfeeding duration among a representative population from 43 states and the District of Columbia. We modeled the likelihood of never initiating breastfeeding by respondent's age, race and ethnicity, language, marital status, household income, educational attainment, parity and insurance status. We also compared sources of information and education for respondents who never breastfed to those who breastfed up to 6 months.ResultsAmong 142,643 new mother respondents, representing an estimated population of 7,426,725 birthing individuals, 12.6% never breastfed, 60.4% reported breastfeeding at 3 months and 54.7% at 6 months. While 75.8% of college graduates reported breastfeeding at 3 months, this was only 37.8% of respondents with high school or less. Among those with the lowest six-month rates were non-Hispanic Black participants (36.3%) and those age < 20 (25.5%). Respondents with Medicaid coverage for their delivery were 25% more likely to have never breastfed than the privately insured. Respondents reporting household income <$20,000 were 57% more likely to have never breastfed as compared to those with household income>$85,000. While 64.1% of those breastfeeding at 6 months reported receiving information from "my" doctor', this was only 13.0% of those who never breastfeed.DiscussionImproved breastfeeding rates could have significant effects on reducing health disparities in the United States. Clinical and public health policy initiatives need to include culturally sensitive breastfeeding education before and after childbirth, with psychological and direct support from obstetrics and primary care providers. Health plans should support home and community-based in-person and telelactation consulting services. Public policies such as paid family and medical leave and workplace accommodations will also be critical. Given the huge implications of breastfeeding rates on the development of infant immune defenses and a healthy microbiome, improving breastfeeding rates should be a much more important public health priority in the United States.